The Global Market for International Students: American Perspectives - Douglass, John; Edelstein, Richard (International Higher Education, 2010)
Though the United States is the number one destination for international students, a shift to other countries might occur because of an explosion of a demand for higher education worldwide as well as an emergence of new competitors. Some countries use higher education to accept educated immigrants for national workforce. Foreign students, who often used to choose to stay in the US after their graduation, are going back to their home countries. Therefore, the United States should set a national strategy on international higher education.